Recent advances in interventional cardiology for coronary artery disease: a systematic literature review - Coronel Mite, Ana Paula (2024)
Recent advancements and innovations in interventional cardiology have already revolutionized coronary artery disease (CAD) treatment and management. Interventional cardiology is a new hope for CAD patients because its evolution has improved disease symptoms. We aimed to explore the integration of diagnostic, therapeutic, and risk management innovations against CAD. In diagnostic advancements, we aimed to discuss the evolution of imaging techniques such as MRI, echocardiography, positron emission tomography (PET), and coronary computed tomography angiography (CCTA), focusing on their unique benefits in the early detection and assessment of CAD. Interventional techniques, notably percutaneous coronary intervention (PCI) innovations, have evolved, incorporating bioresorbable vascular scaffolds, drug-eluting stents, and advanced imaging technologies to enhance procedural success and patient outcomes. Moreover, post-PCI care advancements, including newer antiplatelet agents and PCSK9 inhibitors, have contributed to more personalized and effective CAD management strategies. This paper will also discuss significant strides made in interventional cardiology, underscoring a future where integrated approaches continue to advance patient care in CAD.